Corrected Count Increment Analysis After Thrombocyte Apheresis Transfusion At Wahidin Sudirohusodo Hospital - Rezky Andika Putry; Agus Alim Abdullah; Rachmawati A. Muhiddin (International Journal of Health and Pharmaceutical (IJHP), 2025)
Background: Platelet transfusion plays a role in preventing and treating bleeding in patients with thrombocytopenia. Transfusion failures can sometimes reach 24-44%. The success of platelet transfusion is assessed using several formulas, including Post-transfusion Platelet Increment (PPI), Percentage Platelet Recovery (PPR), and Corrected Count Increment (CCI). CCI is more accurate and most widely used to assess transfusion success. Transfusion is considered successful if the CCI value one hour after transfusion is ≥ 7.5x10^9/µL or ≥ 4.5 x10^9/µL after 24 hours. Purpose: The aim of this study was to analyze the effectiveness of platelet transfusion, using Corrected Count Increment (CCI) after apheresis platelet transfusion in patients with thrombocytopenia and identify factors that influence this outcome, such as age, gender, and underlying diagnosis at Wahidin Sudirohusodo Hospital Makassar. Methods: This study is a retrospective study by taking secondary data from medical records of patients aged ≥ 18 years, who having weight and height / length data and routine blood counts results for thrombocytopenia <150,000 / µL at Wahidin Sudirohusodo Hospital Makassar from January 2023 to December 2023. The research sample was analyzed using the results of CCI calculations using data processing software. Data analysis using the Kolmogorov-Smirnov test for data normality, the chi Square test, Wilcoxon statistical test results are significant if the p-value <0.05. Results: The results of the data analysis found proportion of CCI after apheresis platelet transfusion was found to be significantly higher (p < 0.001) in the group with increased platelet values. The results of CCI analysis with gender, age, malignant and non-malignant diagnoses showed no significant relationship (p > 0.05). Conclusion: In this study, the effectiveness of apheresis thrombocyte transfusion can be assessed by CCI, which is influenced by height and weight, as well as an increase in platelet values. There is no relationship between gender, age and diagnosis (malignancy and non-malignancy) with CCI values.